Navigating Academia Women's Stories of Success and Struggle - A Call to Action - Phaswana-Mafuya, Refilwe Nancy (UJ Press, 2023)
This book is a vital resource for promoting transformation and radical change in academia, offering perspectives, strategies and approaches that can be used in addressing persistent gender inequities in the field. Readers from all walks of life can glean valuable lessons from this remarkable work, allowing them to be inspired and empowered" Prof Olive Shisana, CEO of Evidence Based Solutions and Honorary Professor, University of Cape Town. There are limited books on real-life experiences of women in the workplace let alone in academia for women, by women, with women. This book is the first of its kind as it contains a unique collection of 16 powerful and inspiring stories of success and struggle of women in academia across age groups, career stages, disciplines, and geographies, that will never leave you the same. It offers a platform for validating African women's experiences and heeding their voices which are hardly given any audience in many spaces. You will experience a mixed set of emotions as you celebrate women's resilience, contributions made, and valuable insights shared, but also realize the dehumanizing experiences that women had to go through, and the extraordinary effort it took for them to survive and thrive in non-diverse academic environments. The book offers multiple perspectives, diverse experiences, and rich lessons derived from challenges experienced, and strategies employed, to empower the next generation. Further, the book goes beyond simply highlighting women's struggles; it also calls for a bold and radical call to change the status quo so that future generations don't have to go through the same turmoil. The insights provided in this book have implications for attracting, advancing, and retaining African women in academia. Professor Refilwe Nancy Phaswana-Mafuya (PhD, PGD (Epi), MSc (Epi)) is a qualified epidemiologist and public health scientist. She is the director of the South African Medical Research Council/University of Johannesburg Pan African Centre for Epidemics Research (PACER) Extramural Unit and a professor of epidemiology and public health, Faculty of Health Sciences, University of Johannesburg. Prior to joining the University of Johannesburg, she served as the Deputy Vice Chancellor Research and Innovation at North West University for three years. Professor Phaswana-Mafuya also worked as Acting Executive Director, Research Director, and Chief Research Manager at the Human Sciences Research Council for almost 13 years, among others.